Revenue and Operational Costs Impact on Net Profit: A Quantitative Analysis: Dampak Pendapatan dan Biaya Operasional terhadap Laba Bersih: Analisis Kuantitatif - Ananda, Kiki Resky; Machmud, Mulyana; Hasan, Hamida (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to investigate the influence of income and operational costs on net profit at a specific organization. Employing a quantitative approach with descriptive and verificative methods, linear regression is utilized for data analysis. The results reveal a positive and significant impact of income on net profit (t = 10.629, p < 0.05), while operational costs exhibit a negative and inversely significant relationship (t = -3.707, p > 0.05). The F-test indicates both income and operational costs significantly contribute to net profit (F = 289.333, p < 0.05). This research sheds light on the intricate dynamics between financial variables, providing valuable insights for practitioners and scholars in the field. Highlights: Quantitative Exploration: Utilizing linear regression for a thorough examination of the financial dynamics. Positive Income Influence: Demonstrating a significant positive effect of income on net profit. Operational Cost Dynamics: Unveiling a notable negative and inversely significant relationship between operational costs and net profit. Keywords: Income, Operational Costs, Net Profit, Regression Analysis, Financial Impact